2006
DOI: 10.1073/pnas.0508452103
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 protease flaps spontaneously open and reclose in molecular dynamics simulations

Abstract: We report unrestrained, all-atom molecular dynamics simulations of HIV-1 protease that sample large conformational changes of the active site flaps. In particular, the unliganded protease undergoes multiple conversions between the ''closed'' and ''semiopen'' forms observed in crystal structures of inhibitor-bound and unliganded protease, respectively, including reversal of flap ''handedness.'' Simulations in the presence of a cyclic urea inhibitor yield stable closed flaps. Furthermore, we observe several even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
451
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(490 citation statements)
references
References 35 publications
37
451
0
2
Order By: Relevance
“…That these conformational changes correspond to channel opening is supported by SCAM experiments upon agonist binding (10,19). Our study provides atomic-scale mechanistic insight to nAChR in particular and contributes to the understanding of spontaneous conformational changes in protein function and regulation (29)(30)(31) in general.…”
Section: Resultssupporting
confidence: 56%
“…That these conformational changes correspond to channel opening is supported by SCAM experiments upon agonist binding (10,19). Our study provides atomic-scale mechanistic insight to nAChR in particular and contributes to the understanding of spontaneous conformational changes in protein function and regulation (29)(30)(31) in general.…”
Section: Resultssupporting
confidence: 56%
“…For this reason, we extensively used these parameters on a variety of systems not discussed here before making this report. For example, the improved glycine parametrization was important in our recent simulations of HIV-1 protease 70 , where glycine rich "flaps" play an essential role in protease dynamics. Another study 69 reported a hybrid replica exchange method, where ff99SB was used to test the methodology based on conformational sampling of polyalanine peptides of varying lengths.…”
Section: Discussionmentioning
confidence: 99%
“…A related approach directly compares spectral density components J(ω), 16 whereby the extraction of spectral densities from the experiment requires additional experiments or makes additional assumptions. 29 Here, we report the results of molecular dynamics trajectories of the well-characterized protein ubiquitin computed in the AMBER software package, 30 using both the AMBER99 31 and the modified AMBER99SB 24,25 force fields. Several sets of experimental NMR spin relaxation data have been published for ubiquitin, [32][33][34][35][36] making it a valuable model system for assaying the quantitative accuracy of the MDderived NMR relaxation parameters.…”
Section: Introductionmentioning
confidence: 99%